A ROMAN REPUBLICAN OPENWORK BELT PLATE FROM A SANCTUARY GURZUFSKOE SEDLO: THE PARALLELS TO CASTILLEJO FINDS - Maria V Novichenkova (Journal of Ancient History and Archaeology)
A paper is devoted to a rare find of a Roman bronze openwork belt plate with the preserved skin residues found in a mountain sanctuary Gurzufskoe Sedlo together with the items of the Roman military equipment principally dated by the Late Republican – Early Principate periods. It’s finding in a barbarian sanctuary along with the items of Roman Republican equipment is associated with the participation of Tauri tribes in the military actions against Rome in the Black Sea region during the first half of a 1st century BC. It is possible to study the features of the construction and decor elements of an item due to a good state of its preserve.